Personalized car parking system - Chai, Chin Yee (2020)
As the number of vehicles start to outnumber parking space in major city and limitation of existing smart parking system, drivers with special need getting more difficult to find car parking space based on their requirements. This project is a mobile application for showing location of car parking space in parking facility. It will provide user location of parking space, information of parking facility and current availability of parking as well. User able to filter and view different types of parking spaces such as parking for disabled and ladies’ parking space. Since some feature of existing smart parking technology is well suited for this project, it is therefore implemented in the project. From the design point of view, user interface are designed to have simple, clean structure and easy to learn instruction to guide user. This project will minimize user interaction to application as the target user are driver who unable to perform interaction activity by maximize automation of functionality. The filter car parking focus on matching the requirement entered by user and display filtered parking space to them. Since internet connection in closed parking facility are usually low, offline database are implemented in this application.